Associations between indicators of self-rated health, cognitive function, risk of cognitive impairment, and dementia: A coordinated data analysis - Eileen K Graham; Kayla Garner; Emorie D Beck; Kathryn L Jackson; Jing Luo; Gabrielle N Pfund; Tomiko Yoneda; Rongxin Cheng; Adam Nissen; Anne Zola; Chloe Fawns-Ritchie; Lily Pieramici; et al. (The Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 2026)
Abstract Objectives A growing body of literature suggests that self- or patient- reported health may be associated with objective health outcomes. Self-reported health could thus be a non-invasive and low-cost way of identifying who is at risk of poor health in later life. However, no prior study has systematically examined this relationship using multiple large datasets. The goal of the current study was thus to examine the extent to which self-rated health was associated with cognitive function, a distinct outcome rather than an aspect of health itself. Methods Using a coordinated data analysis (CDA) methodological framework, we identified 15 longitudinal datasets comprising over 140,000 participants representing 38 countries that met our analytic inclusion criteria. Our preregistered analyses tested 1) whether self-rated health was associated with cognitive function both concurrently and at longitudinal follow-up, 2) the odds of developing cognitive impairment or dementia over the course of the study, and 3) whether these associations persisted net of demographic and health covariates. Results Across nearly all datasets, higher self-rated health was associated with better cognitive function (both concurrently and longitudinally) and lower odds of developing dementia, over and above the effects of chronic conditions. Age moderated some effects, such that these associations may be strongest among older adults. Discussion The implications of these findings are discussed in terms of the predictive utility of single-item subjective health indicators on downstream health outcomes and the benefits of using CDA in aging research.